A Prospective Study on HbA1c, Lipid Profile and Genitourinary Infections in Controlled Versus Uncontrolled Diabetic Patients - P. S, Aswathi; Krishnan, Athira; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, leading to significant metabolic complications. Poor glycemic control exacerbates these complications, including alterations in lipid profiles and an increased susceptibility to infections, particularly in the genitourinary system. Aim: This study aimed to compare HbA1c levels, lipid profiles and the prevalence of genitourinary infections in patients with controlled (HbA1c<7.0%) versus uncontrolled (HbA1c≥7.0%) Type 2 Diabetes Mellitus (T2DM). Materials and Methods: A prospective observational study was conducted at a tertiary care hospital, involving 120 patients diagnosed with T2DM. Participants were divided into two groups based on their HbA1c levels: controlled and uncontrolled. Data on HbA1c, lipid profiles and the occurrence of genitourinary infections were collected and analyzed. Results: The study included 120 participants, comprising 45.83% males and 54.17% females, with a mean age of 62.52 years. The mean HbA1c was 9.15%, indicating poor glycemic control; 73.33% of participants were in the uncontrolled group, with a mean HbA1c of 10.16%, while 26.66% were in the controlled group, with a mean HbA1c of 6.35%. Fasting Blood Glucose (FBG) levels in females ranged from 78 to 786 mg/dL, with a mean of 185.76 mg/dL, whereas in males, the range was 68 to 270 mg/dL, with a mean of 151.94 mg/dL. Conclusion: These findings emphasize the importance of maintaining stringent glycemic control in diabetic patients to optimize lipid profiles and reduce the risk of genitourinary infections. Effective management of HbA1c is crucial for mitigating these associated risks in T2DM patients.
Keywords: HbA1c; Lipid Profile; Genitourinary Infections; Diabetes mellitus